Trade and the COVID-19 Pandemic : Lessons from French Firms - Brussevich, Mariya; Papageorgiou, Chris; Wibaux, Pauline (Washington, D.C. : International Monetary Fund, 2022)
This paper uses granular customs data from France to investigate propagation of the COVID-19 shock along the supply chains in 2020. It quantifies the effect of the COVID-19 shock on trade adjustment and identifies mitigating and amplifying factors contributing to French firmsa' heterogeneous adjustment paths. Early in the pandemic, firms mainly responded to global lockdowns and spread of the virus by reducing trade volumes (intensive margin) as opposed to exiting from import and export markets (ex-tensive margin). However, adjustment along the extensive margin played a more important role in trade with developing countries. It is shown that the impact of lockdowns was stronger for final consumer goods and the trade recovery was predominantly demand-driven. More automated, inventory-intensive, older, and medium-sized firms were more insulated from the shock, whereas firmsa' reliance on air transportation for shipping goods amplified the shock. Trade bans and promotion measures implemented by governments in response to the pandemic had little impact on aggregate trade flows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: COVID-19; Firm Behavior; Supply Chains Disruptions; Trade